Affect trumps age: A person-in-context relational view of age and motivation in SLA. (July 2016) - Pfenninger, Simone E; Singleton, David
Recent findings (see, for example, Muñoz and Singleton, 2011) indicate that age of onset is not a strong determinant of instructed foreign language (FL) learners' achievement and that age is intricately connected with social and psychological factors shaping the learner's overall FL experience. The present study, accordingly, takes a participant-active approach by examining and comparing second language (L2) data, motivation questionnaire data, and language experience essays collected from a cohort of 200 Swiss learners of English as a foreign language (EFL) at the beginning and end of secondary school. These were used to analyse (1) whether in the long run early instructed FL learners in Switzerland outperform late instructed FL learners, and if so the extent to which motivation can explain this phenomenon, (2) the development of FL motivation and attitudes as students ascend the educational ladder, (3) the degree to which school-level variables affect age-related differences, and (4) learners' beliefs about the age factor. We set out to combine large-scale quantitative methods (multilevel analyses) with individual-level qualitative data. While the results reveal clear differences with respect to rate of acquisition in favor of the late starters, whose motivation is more strongly goal- and future-focused at the first measurement, there is no main effect for starting age at the end of mandatory school time. Qualitative analyses of language experience essays offer insights into early and late starters' L2 learning experience over the course of secondary school, capturing the multi-faceted complexity of the role played by starting age.